Personalized medicine in genetic epilepsies – possibilities, challenges, and new frontiers. (1st August 2020) - Helbig, Ingo; Ellis, Colin A.
Abstract: Identifying the optimal treatment based on specific characteristics of each patient is the main promise of precision medicine. In the field of epilepsy, the identification of more than 100 causative genes provides the enticing possibility of treatments targeted to specific disease etiologies. These conditions include classical examples, such as the use of vitamin B6 in antiquitin deficiency or the ketogenic diet in GLUT1 deficiency, where the disease mechanism can be directly addressed by the selection of a specific therapeutic compound. For epilepsies caused by channelopathies there have been advances in understanding how the selection of existing medications can be targeted to the functional consequences of genetic alterations. We discuss the examples of the use of sodium channel blockers such as phenytoin and oxcarbazepine in the sodium channelopathies, quinidine in KCNT1 -related epilepsies, and strategies in GRIN-related epilepsies as examples of epilepsy precision medicine. Assessing the clinical response to targeted treatments of these conditions has been complicated by genetic and phenotypic heterogeneity, as well as by various neurological and non-neurological comorbidities. Moving forward, the development of standardized outcome measures will be critical to successful precision medicine trials in complex and heterogeneous disorders like the epilepsies. Finally, we address new frontiers in epilepsy precision medicine, including the need to match the growing volume of genetic data with high-throughput functional assays to assess the functional consequences of genetic variants and the ability to extract clinical data at large scale from electronic medical records and apply quantitative methods based on standardized phenotyping language. Highlights: More than 100 single-gene causes of epilepsy are known to date. Epilepsy precision medicine is based on individual patient characteristics. Known anti-seizure medications can target functional consequences in channelopathies. Phenotypic heterogeneity in genetic epilepsies complicates precision medicine trials. Electronic medical records and phenotyping languages provide novel opportunities.